QUALITY OF LIFE, MENTAL ADJUSTMENT AND PSYCHOLOGICAL REHABILITATION OF MOTHERS OF CHILDREN WITH EPILEPSY - N. V. Semakina; V. A. Mikhailov; M. V. Zlokazova (Эпилепсия и пароксизмальные состояния)
Aim. To assess the quality of life and mental adjustment of mothers of children with epilepsy; to further specify the areas of psychological rehabilitation.Materials and methods. One hundred and twenty women who had children with epilepsy were studied. Clinical assessment of their mental state and their psychological condition were performed using the following instruments: the WHOQOL-BREF, the Stigmatization-of-Patients-with-Epilpesy questionnaire (Wasserman LI, Mikhailov VA), the State-Trait Anxiety Inventory (STAI), the Zung Anxiety Rating Scale (Z-CDS), the Level-of-SocialFrustration questionnaire (Wasserman LI), the Coping Strategy Indicator (Amirkhan D), and the Value Survey (Rokeach M).Results. We found symptoms of anxiety in 51 women (42.5%) and symptoms of neurotic disorders in 34 women (28.3%); among the latter, neurasthenia was diagnosed in 8 women and prolonged depression – in 26 women. The symptoms were accompanied by dissatisfaction with their quality of life, social frustration, maladjustment, high selfstigma due to the child’s disease, hyper-social attitudes and preference for choosing irrational coping strategies in difficult situations.Conclusion. The results indicate the ways of psychological rehabilitation (i.e. psychological education and prevention) of such mothers to improve their mental adjustment and stress resistance.